Differences in mortality rate among patients hospitalized with severe COVID‐19 according to their body mass index - Alejandra Albarrán‐Sánchez; Claudia Ramírez‐Rentería; Juan C. Anda‐Garay; Maura E. Noyola‐García; Paolo Alberti‐Minutti; Guillermo Flores‐Padilla; Luis A. Guizar‐García; Carlos E. Contreras‐García; Daniel Marrero‐Rodríguez; Keiko Taniguchi‐Ponciano; Moises Mercado; Aldo Ferreira‐Hermosillo (Obesity Science & Practice, 2022)
Abstract Background Obesity has been described as a risk factor for COVID‐19 severity and mortality. Previous studies report a linear association between BMI and adverse outcomes, meanwhile in other critical illness, excessive fat tissue is related to improved survival. Whether different BMI is related with the survival of patients with severe COVID‐19 deserves further analysis. Objective To determine the mortality rate among hospitalized patients with severe COVID‐19 stratified according to BMI. Methods The clinical files of all patients hospitalized from March to December 2020 with a positive PCR test for SARS‐CoV‐2 discharged due to improvement or death, were analyzed. A mixed effects logistic regression was carried out to determine which clinical and biochemical characteristics and comorbidities were associated with in‐hospital mortality. Results The cohort consisted of 608 patients with a median age of 59 years (interquartile ranges, IQR 46–69 years), median BMI of 28.7 kg/m2 (IQR 25.4–32.4 kg/m2), 65.5% were male. In‐hospital mortality rate was 43.4%. Of the cohort 0.8% had low weight, 20.9% normal weight, 36.0% overweight, 26.5% obesity grade I, 10.2% obesity grade II and 5.6% obesity grade III. Mortality rate was highest in patients with low weight (80%), followed by patients with obesity grade III (58.8%) and grade II (50.0%). Overweight and underweight/obesity grade III were associated with higher mortality (OR of 9.75 [1.01–1.10] and OR 4.08 [1.64–10.14]), after adjusting by sex and age. Conclusions The patients in the underweight/overweight and grade 3 obesity categories are at higher risk of COVID‐19 related mortality, compared to those with grade I or II obesity.